Anthropometric Determinations of Umbilical Position in Iraqi Adults - Mazin Abdulsattar Abdulla; Saja Mahmood Ali Fahad (Indian Journal of Plastic Surgery)
Introduction Umbilicus is an important surface landmark on the anterior abdominal wall in addition to its aesthetic and psychological effect. Objectives The objective of the study is to determine the position of umbilicus in Iraqi adults to provide a guide for the neoumbilicus in abdominoplasty. Subjects and Methods This is an observational study performed on 100 volunteers with no abdominal wall abnormality. Measurements included weight, height, body mass index (BMI), distance from xiphoid to umbilicus, distance from xiphoid process to pubic symphysis, distance from xiphoid process to both anterior superior iliac spine (ASIS), distance from pubic symphysis to umbilicus and from pubic symphysis to xiphisternum, distance of umbilicus to both ASIS, and distance of umbilicus to interspinous line and to inter-anterior hypochondrium line. Results The study included 100 volunteers, with 50% male and 50% female whose age ranges between 18 to 60 years. The results were a follows: distance from xiphoid process to umbilicus and distance from xiphoid process to pubic symphysis were 18.03 ± 3.25 cm and 32.21 ± 4.64 cm, respectively; distances from xiphoid process to right ASIS and left ASIS were 25.95 ± 5.72 cm and 25.84 ± 6.02 cm, respectively; distance from pubic symphysis to umbilicus was 17.66 ± 3.12 cm; distance of umbilicus to interspinous line was 9.25 ± 1.84 cm. The distance from umbilicus to inter anterior hypochondrium line was 9.905 ± 2.19 cm. Conclusion These measurements can determine the neoumbilicus position, reduce practical mistakes, and improve postsurgical outcomes.